2023
DOI: 10.3390/ijerph20031745
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Pollution: Chemical Characterization and Impact on Wildlife

Abstract: Microplastics are small pieces of plastic that are less than 5 mm in size and can be found in most environments, including the oceans, rivers, and air. These small plastic particles can have negative impacts on wildlife and the environment. In this review of the literature, we analyze the presence of microplastics in various species of wildlife, including fish, birds, and mammals. We describe a variety of analytical techniques, such as microscopy and spectrometry, which identify and quantify the microplastics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…Photodegradation is a process that can be used to break down microplastics using light energy [ 89 ]. Chemical digestion is a process that can be used to remove microplastics from samples by treating them with reagents such as KOH, HNO 3 , or H 2 O 2 to dissolve the matrix and separate the microplastics by filtration or gravimetrically [ 91 ]. Digestion can be used to remove organic matter from samples containing microplastics, and protocols can vary depending on the sample type and the microplastic being analyzed.…”
Section: Waste Management Of Plasticmentioning
confidence: 99%
See 1 more Smart Citation
“…Photodegradation is a process that can be used to break down microplastics using light energy [ 89 ]. Chemical digestion is a process that can be used to remove microplastics from samples by treating them with reagents such as KOH, HNO 3 , or H 2 O 2 to dissolve the matrix and separate the microplastics by filtration or gravimetrically [ 91 ]. Digestion can be used to remove organic matter from samples containing microplastics, and protocols can vary depending on the sample type and the microplastic being analyzed.…”
Section: Waste Management Of Plasticmentioning
confidence: 99%
“…Microorganisms have the potential for electricity production, which can be tapped using microbial fuel cells. Microbial Fuel Cells (MFC) are biochemical devices that produce electricity during microorganisms' aerobic or anaerobic respiration [ 91 ]. The MFC has been considered an innovative and environmentally friendly bioenergy technology with great potential for generating electricity for energy storage [ 93 ].…”
Section: Waste Management Of Plasticmentioning
confidence: 99%
“…It is reported that the United Nations Environmental Program (UNEP) stated that the number of microbeads in an exfoliating gel could almost be the same number of plastics used in packaging the product [124]. With microbeads abundant in the water, aquatic animals can ingest these plastics, which can threaten their lives, and potentially human health when taken up through the food chain, as MPs have been found to have the capability to translocate into the circulatory system and accumulate in human lungs, liver, and brain [80,119,[125][126][127]. This information on microbeads prompted some countries to enact laws to prohibit microbeads in cosmetic and cleaning products.…”
Section: Microplastics Legislationmentioning
confidence: 99%
“…The plastics accumulated and dispersed in the environment are transformed overtime into very small particles, the so‐called micro/nanoplastics, that not only contribute significantly to the emissions of greenhouse gas responsible for climate change, [4] but also have harmful, both acute and chronic, effects on humans, such as the occurrence of contact dermatitis. Several studies have shown that microplastics are accumulated in our body [5] causing health effects such as diabetes, obesity and infertility and have also been shown to act as carcinogens [5,6] …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that microplastics are accumulated in our body [5] causing health effects such as diabetes, obesity and infertility and have also been shown to act as carcinogens. [5,6] PET, as most of other plastic products, is one of the most widely produced thermoplastic polymers for packaging, [7] and its chemical cleavage into its raw materials through environmentally sound solution for its depolymerization is therefore necessary. [8,9] A valid proposed solution is the enzymatic degradation [8,[10][11][12][13] throughout a mesophilic bacterium recently isolated that is capable of degrading PET, named Ideonella sakaiensis 201-F6.…”
Section: Introductionmentioning
confidence: 99%